Pengaruh Financial Distress, Leverage dan Intensitas Modal terhadap Konservatisme Akuntansi : (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024) - Aghnizka Dewi Asya; Melan Sinaga (AKUNTANSI 45, 2026)
This study aims to analyze the effect of financial distress, leverage, and capital intensity on accounting conservatism in mining companies listed on the Indonesia Stock Exchange. Accounting conservatism is an important principle in financial reporting as it helps reduce information asymmetry and potential opportunistic behavior by management. This study uses a quantitative approach with secondary data obtained from financial statements of mining companies. The population consists of 40 mining companies, and the sampling technique used is purposive sampling, resulting in 200 observation data. The analytical method employed is multiple linear regression analysis using SPSS version 25. The results indicate that leverage has a significant negative effect on accounting conservatism, suggesting that companies with higher debt levels tend to apply lower levels of conservatism in financial reporting. Meanwhile, financial distress and capital intensity do not have a significant effect on accounting conservatism. These findings imply that debt structure plays a more dominant role compared to financial condition and asset composition in influencing conservatism practices. This study contributes to the literature by providing empirical evidence on factors affecting accounting conservatism in the mining sector and can be used as a reference for investors, regulators, and future researchers.